Cell-Free Enzymatic Conversion of Spent Coffee Grounds Into the Platform Chemical Lactic Acid - Kopp, Dominik; Willows, Robert D.; Sunna, Anwar (Frontiers in Bioengineering and Biotechnology, 2019)
The coffee industry produces almost 10 billion kg beans per year and generates high amounts of different waste products. Spent coffee grounds (SCG) are an industrially underutilized waste resource, which is rich in the polysaccharide galactomannan, a polysaccharide consisting of a mannose backbone with galactose side groups. Here, we present a cell-free reaction cascade for the the conversion of mannose, the most abundant sugar in SCG, into L-lactic acid. The enzymatic conversion is based on a putative oxidative mannose metabolism from Thermoplasma acidophilum and uses a previously characterised mannonate dehydratase to convert mannose into lactic acid via 4 enzymatic reactions. In comparison to known in vivo metabolisms the bioconversion is free of phosphorylated intermediates and cofactors. Assessment of enzymes, adjustment of enzyme loadings, substrate and cofactor concentrations and buffer ionic strength allowed the identification of crucial reaction parameters and bottlenecks. Moreover, reactions with isotope labelled mannose enabled the monitoring of intermediates and revealed a reverse flux in the reaction cascade. Finally, 4.4 ± 0.1 mM lactic acid was produced from 14.57 ± 0.7 mM SCG-derived mannose. While the conversion efficiency of the process can be further improved by enzyme engineering, the process demonstrates the first multi-enzyme cascade for the bioconversion of spent coffee grounds.